Analysis of the status and risk factors for Helicobacter pylori infection and drug resistance in the Lianyungang area, China - Chuchu Yang; Huahui Zhang; Shouying Li; Zhimei Zhang (BMC Gastroenterology)
Abstract Objective Helicobacter pylori (H. pylori) has attracted much attention since its discovery. This bacterium has had a substantial impact on society, the economy, and public health. In recent years, with the continuous increase in drug resistance in H. pylori and the emergence of multidrug resistant strains, the existing diagnostic and treatment options are no longer able to meet clinical needs, so we need to understand the dynamically changing nature of drug resistance of H. pylori in our region. This study collected stool samples from community residents in Lianyungang to analyse the local H. pylori infection status, resistance to commonly used antibacterial agents, and risk factors to provide a reference for local clinical empirical treatment. Methods: Human stool samples from Lianyungang residents were collected, the DNA of H. pylori in the positive samples was extracted, the sites of mutated genes were determined by PCR and nucleic acid mass spectrometry, and genotypes of cytotoxin-associated gene A (CagA) and vacuolating cytotoxin A (VacA) were tested. The resistance rates of local H. pylori strains to five antibacterial agents, levofloxacin, clarithromycin, furazolidone, amoxicillin, and tetracycline, were collected, and the risk factors for drug resistance were analysed statistically based on questionnaire results. Results: A total of 221 residents with qualified stool samples were enrolled. The infection rate was 25.3%. DNA was extracted from 56 H. pylori samples. Among them, only 17 H. pylori strains were sensitive to all five antibiotics, and a total of five drug resistance patterns were detected. The main drug resistance patterns were single drug resistance to clarithromycin (30.4%) and double drug resistance to levofloxacin + clarithromycin (21.4%). The levofloxacin resistance mutations were mainly located at N87K and D91Y of the gyrA sequence, and the clarithromycin resistance mutations were mainly located at A2143G in the 23S rRNA sequence. Age, gastrointestinal symptoms, and previous history of H. pylori infection were risk factors for resistant H. pylori. A previous history of H. pylori infection was an independent risk factor for the development of drug resistance in H. pylori. Conclusion: The H. pylori infection rate in the Lianyungang area is lower than the national rate, but the rates of resistance to levofloxacin and clarithromycin are quite high. Drug sensitivity testing is needed to provide more accurate individualized treatment and improve the eradication rate of H. pylori. Continuous monitoring of local antibiotic resistance patterns remains the first choice for empirical treatment.